1997
DOI: 10.2741/a224
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas transplantation indications clinical management and outcomes

Abstract: Although many advances have been made, pancreas transplantation still poses several challenges to the surgeon, internist and patient. With success rates now above 80% and improving yearly, diabetic patients must make a major life-style decision when considering a pancreas transplant. The main concerns are will the benefits of insulin-independence off-set the risks of surgery and immunosuppression. For diabetics near dialysis and considering a kidney transplant, the decision may not be as difficult. However, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…TP53-governed apoptosis is considered the main cause of ionizing radiation-induced cell death, despite the fact that some cancer cells undergo TP53-independent apoptosis [6,7]. Therefore, the radioresistant tumor cells are often accompanied by TP53 mutation or repression, high levels of B-Cell CLL/ Lymphoma 2 (BCL2), or inhibition of the other apoptosis-related genes [8][9][10][11][12]. In NPC, it has been suggested that latent membrane protein 1 (LMP1), encoded by Epstein-Barr virus, blocks apoptosis and thereby facilitates radioresistance of the tumor cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…TP53-governed apoptosis is considered the main cause of ionizing radiation-induced cell death, despite the fact that some cancer cells undergo TP53-independent apoptosis [6,7]. Therefore, the radioresistant tumor cells are often accompanied by TP53 mutation or repression, high levels of B-Cell CLL/ Lymphoma 2 (BCL2), or inhibition of the other apoptosis-related genes [8][9][10][11][12]. In NPC, it has been suggested that latent membrane protein 1 (LMP1), encoded by Epstein-Barr virus, blocks apoptosis and thereby facilitates radioresistance of the tumor cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…TP53-governed apoptosis is considered the main cause of ionizing radiation-induced cell death, despite the fact that some cancer cells undergo TP53-independent apoptosis (Afshar, Jelluma et al, 2006, Strasberg Rieber, Zangemeister-Wittke et al, 2001. Therefore, the radioresistant tumor cells are often accompanied by TP53 mutation or repression, high levels of BCL2, or inhibition of the other apoptosis-related genes (Brown & Wouters, 1999, Leone, Humar et al, 1997, McGill & Fisher, 1997, Reed, Miyashita et al, 1996, Yaes, 1989. In NPC, it has been suggested that latent membrane protein 1 (LMP1), encoded by Epstein-Barr virus, blocks apoptosis and thereby facilitates radioresistance of the tumor cells (Lu, Ma et al, 2008).…”
Section: Introductionmentioning
confidence: 99%